Switchable dual-band bandpass filter based on stepped impedance resonator with U-shaped defected microstrip structure for wireless applications - Mussa Mabrok; Zahriladha Zakaria; Yully Erwanti Masrukin; Tole Sutikno; A. R. Othman; Nurhasniza Edward (Universitas Ahmad Dahlan, 2019)
This paper presents a new technique in designing the switchable dual-band bandpass filter at 2.4 GHz and 3.5 GHz for WLAN and WiMAX applications. Wideband bandpass filter designed based on stepped impedance resonator at frequency of 3 GHz. To eliminate the interference from existing system that operates in the same frequency band, a defected microstrip structure applied and implemented to produce the notch response. In order to generate the switchable characteristic, the PIN diode was introduced at the dual-band filter. It exhibits that the measured results for switchable attributes when the diode is at OFF state, the wide passband is produced with the fractional bandwidth of 62.1 % centered at 2.9 GHz. Meanwhile, for the diode in ON state, the dual-passband has produced which centered at 2.5 GHz and 3.45 GHz. The experimental results showed good agreement with the simulation results. This structure is very useful for wireless communication systems and its applications.